A simulation study around investigating the effect of polymers on the structure and performance of a perovskite solar cell - Seyyed Reza Hosseini; Mahsa Bahramgour; Nagihan Delibas; Aligholi Niaei (Journal of Optoelectronical Nanostructures, 2022)
Polymers are a very vast classification of materials thatpossess a lot of applications in various industries. Forinstance, they have application in structure modificationof the perovskite solar cells (PSCs). Polymers’application in perovskite solar cells can be divided intotheir usage as hole-transporting materials (HTMs) andthe ultrathin interfaces between hole transportingmaterials and the perovskite layer. In the presentresearch, we tried to highlight this application from thesimulation perspective using SCAPS-1D software. Forthis purpose, this study investigates the effect of usingdifferent polymeric HTMs and interfaces from thephotovoltaic parameters view. The total PSC structurewas in the form of Au (Back contact)/ HTM/ polymericInterface (if there are)/ CH3NH3PbI3 (absorber)/ TiO2(Electron Transporting Material: ETM)/FTO (counterelectrode). Results represented the best hole transportingmaterial and interface as PEDOT:PSS and P3HT layers.The final efficiency was obtained at 18.77% with theoptimal mentioned layers’ materials.